The effectiveness of physical exercises in the treatment and prevention of osteoporosis in women - Rebello, Eduardo Shelmo de Oliveira (2013)
Introduction: Osteoporosis is a disease that afflicts more women in post menopausal stage, is a major public health problem today, with degenerative features and multifactorial, related to genetics and the lifestyle, especially dietary habits and physical activity level. The aim of this study was to review only between the original articles, free, from Brazilian authors, published in the databases SciELO and Lilacs, from January 2000 to December 2009, which are the main areas of expertise of the researchers, the number of articles published nationally and especially its quality. In this literature review, we noted that there are few works that relate physical exercises and treatment of osteoporosis in women in Brazil, most of them were published by physiotherapists and despite showing positive results, longer-lasting studies with specific training and examinations to prove the improvement of bone mineralization, can provide more information about the dynamics of the adaptation of these women to exercise in the long term. We conclude that prevention through appropriate physical activities in childhood and adolescence appears to be of paramount importance and that the positive impact of the practice of any physical activity on quality of life of any individual is indisputable but the effectiveness of physical exercise in improving bone mineralization in women with osteoporosis was rarely broached in the articles reviewed.